2005
DOI: 10.1172/jci24908
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of beryllium-specific, central memory CD4+ T cells in blood determines proliferative response

Abstract: Beryllium exposure can lead to the development of beryllium-specific CD4 + T cells and chronic beryllium disease (CBD), which is characterized by the presence of lung granulomas and a CD4 + T cell alveolitis. Studies have documented the presence of proliferating and cytokine-secreting CD4 + T cells in blood of CBD patients after beryllium stimulation. However, some patients were noted to have cytokine-secreting CD4 + T cells in blood in the absence of beryllium-induced proliferation, and overall, the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 35 publications
6
55
1
Order By: Relevance
“…Proliferation assays were performed using PBMCs and BAL cells (2 ϫ 10 6 cells/well) labeled with 2.0 M CFSE (Molecular Probes) (31,32). The CFSE-labeled cells were cultured at 37°C for 5 days in a humidified 5% CO 2 atmosphere in RPMI 1640 supplemented with 10% heat-inactivated human serum, 20 mM HEPES, 1 mM sodium pyruvate, 100 U/ml penicillin, 100 g/ml streptomycin, and 2 mM L-glutamine (all from Invitrogen Life Technologies) with the addition of either medium, 10 g/ml platebound anti-CD3, or 100 M BeSO 4 .…”
Section: Proliferation Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Proliferation assays were performed using PBMCs and BAL cells (2 ϫ 10 6 cells/well) labeled with 2.0 M CFSE (Molecular Probes) (31,32). The CFSE-labeled cells were cultured at 37°C for 5 days in a humidified 5% CO 2 atmosphere in RPMI 1640 supplemented with 10% heat-inactivated human serum, 20 mM HEPES, 1 mM sodium pyruvate, 100 U/ml penicillin, 100 g/ml streptomycin, and 2 mM L-glutamine (all from Invitrogen Life Technologies) with the addition of either medium, 10 g/ml platebound anti-CD3, or 100 M BeSO 4 .…”
Section: Proliferation Assaymentioning
confidence: 99%
“…Biexponential scaling was used in all dot plots. Because the frequency of beryllium-specific CD4 ϩ T cells in blood tends to be low, we only examined the expression of PD-1 on cytokine-producing cells with frequencies Ն0.04% to ensure an adequate number of events for analysis as previously described (31)(32)(33). The CFSE-blocking experiments were acquired using a FACSCalibur flow cytometer (BD Immunocytometry Systems), and CellQuest Pro software was used to analyze the data.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized Delta Proportion of Cells that Divided (delta PD) marker as sensitive and more acceptable in clinical measurements than previously reported Proliferating Ratio (PD) (17). We demonstrated that PHA and Candida stimulated both CD4 þ and CD8 þ T cells, while only CD4 þ T cells respond to beryllium in vitro because of MHC class II HLA-DP Glu69 mutation (5,33,34). Determination of specific subpopulation of T cells, responding to beryllium, makes this CFSE proliferation technique compatible to BeLPT, and would have great potential to be developed further for early diagnosis of sensitization to beryllium.…”
Section: Discussionmentioning
confidence: 99%
“…Streptavidin-PE was used as a second-step reagent for TCR staining. The lymphocyte population was identified using forward and 90-degree light scatter patterns, and fluorescence intensity was analyzed using a FACSCalibur cytometer (BD Immunocytometry Systems) (30,31).…”
Section: Flow Cytometry and Immunofluorescence Analysismentioning
confidence: 99%